Seven years of experience with treatment of benign paroxysmal positional vertigo with a mechanical rotational chair - Hougaard, Dan Dupont; Valsted, Sebastian Hygum; Bruun, Niels Henrik; Bech, Mathias Winther; Talebnasab, Michel Heide (Frontiers in Neurology, 2022)
Background Throughout the last decade, several mechanical rotational chairs have been developed for diagnostics and treatment of patients with a typical case history of benign paroxysmal positional vertigo. Sparse evidence, however, exists in terms of diagnostic accuracy and treatment efficiency with these mechanical rotational chairs. Also, recommendations for optimal use of these chairs are yet to be determined. Objective Primary objective was to evaluate overall treatment of benign paroxysmal positional vertigo with a mechanical rotational chair and secondary objectives included description of patient- and BPPV characteristics, determination of subjective and objective outcomes, as well as analyzation of recurrence- and recurrence-related risk factors following successful treatment. Methods Retrospective cohort study with 635 patients diagnosed with benign paroxysmal positional vertigo and treated by means of a mechanical rotational chair during a 7-year period from 2014 to 2021 at a tertiary University hospital. Patient- and disease-specific characteristics, treatment and recurrence data were collected through reviewing of patient records. Results The mean number of required treatments was 2.7 when accounting for a six percent treatment failure rate (defined as a need of more than 10 treatments), and 3.7 when not. Bilateral mono-canal affection required 3.8 treatments, unilateral multi-canal 3.5 treatments, and the combination of bilateral and multi-canal affection 5.2 treatments. All these scenarios were associated with significantly higher numbers of required treatments when compared to unilateral mono-canal affection, which required 1.9 treatments. The overall recurrence rate was 25.4 percent. Conclusion A mechanical rotational chair provides successful treatment of benign paroxysmal positional vertigo. Mechanical rotational chairs should primarily be reserved for the treatment of retractable and atypical benign paroxysmal positional vertigo patients. Many aspects of the optimal use of these chairs still require elaborative assessment.